PW 1415 Students 'walk this way' safely to school. (November 2018) - Sidik, Mirjam; Parker, Lukas; Le, Thuong; Bui, Hong
Abstract : AIP Foundation's Walk This Way program in Vietnam has the goal to create environments in which children can walk safely, and decrease the number of child pedestrian injuries and fatalities through education, awareness and advocacy, but also by intervening in environments and infrastructure surrounding schools to make sidewalks and roads safer to navigate. With the construction of Ho Chi Minh City's (Vietnam's largest city) first Bus Rapid Transit underway, this intervention at 37 schools along its corridor responds to the expected transformation of traffic conditions and its associated risk to child pedestrian safety near schools. In the baseline survey of 5291 students uncovered knowledge, attitudes and reported practices related to road rules and travel to and from school. Also, video observations were undertaken of pedestrian sidewalk and crosswalk use. Knowledge of road rules and safe pedestrian behaviors was moderate, but varied widely. 22.8% of students said they had been hit by a vehicle while walking in the last six months; 10.2% occurred near the school and 76.4% by a motorbike. At 14 of the 37 schools there was no sidewalk available for pedestrians and in many cases, these were encroached upon by vehicles and other obstructions. Most schools had 'Children Ahead' signs posted on nearby main roads but none had school zone signage. 33 had zebra crossings nearby, 20 had traffic lights, but none had traffic calming devices such as flashing lights or rumble strips. Unsafe crosswalk and sidewalk practices observed outweighed correct practice. The study revealed that the problem was more than just an issue of knowledge and attitudes, but also environments and infrastructure around the schools. The first phase education component of the program began in late 2017 and will complete in early 2018. Subsequent phases which involve environmental and infrastructural interventions will begin in 2018.